Thermal shock behaviour and failure mechanism of two-kind Cr coatings on non-planar structure. (November 2022) - Hu, Ming; Pan, Mengfei; Shen, Mingli; Guo, Cean; Tang, Yueyang; Yu, Hangjian
Highlights: Failure analysis of Cr coatings by comparative test. The failure difference for Cr coatings on rifling structure of gun barrel is obvious. Residual stress and inherent characteristics of coatings affect the failure degree. Thermal shock failure of the coating occurs in a specific area or location. Relationship between specific areas of rifling structure and residual stress. Abstract: Cr coating is widely used as a protective coating on the inner and outer surface of industrial equipment. However, current researches on Cr coatings are predominantly conducted on plane specimens, and few works have considered the effect of irregular substrates on coatings. The thermal shock behaviour and failure mechanisms of two-kind Cr coatings prepared by electroplating and vacuum arc ion plating on non-planar structure at 900 °C were investigated. The microstructure and crystalline phases of the two-kind Cr coatings were analysed by scanning electron microscopy, energy dispersive spectrometry, and X-ray diffraction. The results indicate that vacuum arc ion plating Cr coating has better thermal shock resistance. There were two typical damaged regions for both Cr coatings, i.e.the concave corner of groove and the convex corner of land. By analysing the thermal shock damage behaviour of the coatings, it is concluded that fatigue stress, thermal mismatch stress, and the inherent properties of the two-kind Cr coatings are the main reasons for the difference in the overall damage degree, and the temperature stress concentration in the concave corner of groove is the cause for the higher degree of thermal shock damage.